Renewable energy, non-renewable energy, economic growth and CO2 emissions in the newly emerging market economies: The moderating role of human capital - Gnangoin, Thierry Yobouet; Kassi, Diby Francois; Edjoukou, Akadje Jean-Roland; Kongrong, OuYang; Yuqing, Dai (Frontiers in Environmental Science, 2022)
The International Energy Agency revealed in its report in 2021 that the world energy-CO2 emission reached its highest peak during that year. This statistic shows the need to set new environmental protection policies and improve the current ones. Hence, our study aims to highlight the leading role of human capital in the fight against climate change. To do so, by using the Feasible Generalized Least Squares and the Two-Stage Least Squares estimators, we analyze the moderating impact of human capital on the link between renewable energy, nonrenewable energy, economic growth, and CO2 emissions in the case of the 20 newly emerging market economies for the period 1990-2021. We find negative effects of renewable energy consumption, industrialization and trade openness on CO2 emissions. We also find positive effects of nonrenewable energy consumption, economic growth, and human capital on CO2 emissions. In addition, our findings reveal that renewable energy consumption and human capital are complementary levers for reducing CO2 emissions, whereas human capital mitigates the detrimental effect of nonrenewable energy consumption on environmental quality. Besides, the results underline that human capital has an inverted U-shaped effect on CO2 emissions. Regarding policy implications, policymakers should emphasize the complementarity between human capital and renewable energy consumption by facilitating the accumulation of human capital towards productive investments and the use of renewable energy technologies in these countries. They should also raise people's environmental awareness by implementing educational reforms, effective environmental awareness campaigns, and government regulatory pressures that help people understand global warming issues and adopt environmentally friendly practices in their daily activities. Finally, policymakers should promote the use of renewable energy rather than non-renewable energy sources in the production of goods and services by obliging countries to integrate green policies into their industrialization and trade openness strategies.